Analisis Sistem Dan Prosedur Pemberian Kredit Konsumtif Pada PD. BPR Bank Buleleng 45: Analisis Sistem Dan Prosedur Pemberian Kredit Konsumtif Pada PD. BPR Bank Buleleng 45 - Putu Megarani Sukarini Putri; Werastuti, Desak Nyoman Sri (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to determine the system and procedure of consumptive  credit granting to PD.  BPR Bank Buleleng 45. PD. BPR Bank Buleleng 45 is the subject of this  research. Descriptive method a qualitative approach  is used in this study . This research result indicates (1) The consumptive credit system of PD. BPR Bank Buleleng 45 is initiated by debtor applying for credit by filling out a form and cmpleting the file. Debtor files are recoded and checked by the administration. Account Officer conducts survey and analysis. Perform risk level analysis by risk management. Management holds credit meetings to make decisions, re-check, make SPK, and disburse credit. The Accounting Department keeps books, loan books, and notes. Dokuments are evaluated and kept by PE Audit. The debtor signs the SPK, receives the money and the loan book.  (2) The procedure for granting consumptive credit to PD. BPR Bank Buleleng 45 is the submission of files, investigation of files, initial interviews, on the spot, credit decision, signing of credit contracts, credit realization, and distribution/withdrawa i of funds.